RELATIONSHIP BETWEEN CREATIVITY, BUSINESS NETWORK AND INDEPENDENCE IN ENTREPRENEURSHIP OF ACEH YOUTH - BADARUDDIN, BADARUDDIN; AZIS, Nasir; SOFYAN, Hizir; BASRI, Hasan (Theoretical and Practical Research in Economic Fields, 2019)
The purpose of this study was to determine the effect of creativity, business Networks and entrepreneurial independence among young people in Aceh. The location of this study was conducted on young and medium-sized business actors in Aceh, the sampling method used non-probability sampling method with purposive sampling technique so that the number of respondents obtained were 170 young entrepreneurs in Aceh. The analytical tool used is Structural Equation Modeling in the model and testing hypotheses and testing a series of relatively complex relationships simultaneously. The results showed that creativity support, business network support, and independence support had a significant influence on entrepreneurship among young people in Aceh. From the results of this study it can be seen that each indicator that forms a latent variable shows the results that meet the criteria, namely the CR value above 1.96 with P-value  that is smaller than 0.05.